Purwarupa Autonomous Mobile Robot dengan Hoverboard dan Sensor RPLIDAR menggunakan Algoritme Hector SLAM dan Navfn - Bambang Gunawan Tanjung; Rizal Maulana; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The number of requests for freight forwarding services has increased every year. This increase in demand was triggered by the escalation of online shopping trends. As a result, many packages need to be managed in the warehouse. For this, an autonomous distribution system is needed in the warehouse so that warehouse management efficiency occurs, especially in time and labor. The system consists of a sensor encoder, IMU GY-521, RPLIDAR A1, and Robot Operating System (ROS). Systems with robotic characteristics like this can be classified as a type of autonomous mobile robot (AMR). The specialty of the research is the application of the hoverboard as a robot propulsion system. The local spatial map creation process is carried out by the Hector SLAM algorithm. Global and local path planning was created using the Navfn algorithm and the Dynamic Window Approach (DWA). For localization and finding the robot's current location, the Extended Kalman Filter (EKF) and Adaptive Monte Carlo Localization (AMCL) algorithms are used. The test results show that the hoverboard can be used in the system as a propulsion system with the ability to carry a maximum weight of 40Kg. The performance of the odometry, IMU, and RPLIDAR sensors get a sensor accuracy count of 99.61%, 81.93%, and 99.84%. For map making, the results obtained accuracy of 80% success using the Hector SLAM algorithm. Unhindered global navigation test achieves 80% accuracy. While local navigation with moving obstacles reaches 80% accuracy.